Perilaku Membuang Sampah Mahasiswa PSKM STIK Bina Husada Palembang - Maria Ulfah Ulfa; Dian Eka Anggreny (HEALTH CARE : JURNAL KESEHATAN, 2022)
Based on the Palembang Sanitation and Planning Office Data, organic waste is a dominates household waste. The percentage of organic waste household waste is added with leaves and is around 49.4%. Meanwhile, the amount of organic waste several markets in Palembang city in 2008 the results of data processing in the Palembang was 785 tons/day or 2317 m3/ day. Objective:Obtain the behavior disposing of waste the students of PSKM STIK Bina Husada Palembang in 2019.This study used a quantitative research method a cross sectional approach and sampling used a total sampling technique. The population were 155 STIK Bina Husada Palembang students with the sample was 60. There was a relationship between attitude and waste disposal behavior with 0.000, OR 4,000. There is a relationship between knowledge and student waste disposal behavior a p-value of 0.001, OR 14.350. There is a sex relationship student waste disposal behavior (Pvalue 0.004, OR 0.098). There is a relationship between the number of trash cans and the behavior of students throwing trash a p-value of 0.000, OR 128,000. Conclusion: There is a relationship between attitude, knowledge, gender, the number of trash cans and the behavior of throwing garbage at STIK Bina Husada Palembang Students in 2019. It is necessary to increase knowledge of counseling and information to waste disposal and provide a sources information or counseling for male and female students so that the students' knowledge is better.